Enhanced Ocular Surface and Intraoral Nociception via a Transient Receptor Potential Vanilloid 1 Mechanism in a Rat Model of Obstructive Sleep Apnea. (10th February 2022) - Kishimoto, Saki; Katagiri, Ayano; Oyamaguchi, Aiko; Sato, Hajime; Toyoda, Hiroki; Niwa, Hitoshi; Bereiter, David A.; Iwata, Koichi; Kato, Takafumi
Highlights: CIH enhances ocular surface and intraoral sensitivity to topical capsaicin. CIH increases the percentage of TRPV1-positive neurons in the TG. CIH increases the ratio of large- to small-sized TRPV1-positive neurons in the TG. CIH increases the number of pERK-IR neurons evoked by capsaicin in Vc. Normoxic conditions reduce the enhanced orofacial pain induced by CIH. Abstract: Obstructive sleep apnea (OSA), characterized by low arterial oxygen saturation during sleep, is associated with an increased risk of orofacial pain. In this study, we simulated chronic intermittent hypoxia (CIH) during the sleep/rest phase (light phase) to determine the role of transient receptor potential vanilloid 1 (TRPV1) in mediating enhanced orofacial nocifensive behavior and trigeminal spinal subnucleus caudalis (Vc) neuronal responses to capsaicin (a TRPV1 agonist) stimulation in a rat model of OSA. Rats were subjected to CIH (nadir O2, 5%) during the light phase for 8 or 16 consecutive days. CIH yielded enhanced behavioral responses to capsaicin after application to the ocular surface and intraoral mucosa, which was reversed under normoxic conditions. The percentage of TRPV1-immunoreactive trigeminal ganglion neurons was greater in CIH rats than in normoxic rats and recovered under normoxic conditions after CIH. The ratio of large-sized TRPV1-immunoreactive trigeminal ganglion neurons increased in CIH rats. The density of TRPV1 positive primary afferent terminals in the superficial laminae of Vc was higher in CIH rats. Phosphorylated extracellular signal-regulated kinase (pERK)-immunoreactive cells intermingled with the central terminal of TRPV1-positive afferents in the Vc. The number of pERK-immunoreactive cells following low-dose capsaicin (0.33 µM) application to the tongue was significantly greater in the middle portion of the Vc of CIH rats than of normoxic rats and recovered under normoxic conditions after CIH. These data suggest that CIH during the sleep (light) phase is sufficient to transiently enhance pain on the ocular surface and intraoral mucosa via TRPV1-dependent mechanisms.